Associations between brominated flame retardants, including polybrominated diphenyl ethers, and immune responses among women in the California Teachers Study - Cauble, Emily L.; Reynolds, Peggy; Epeldegui, Marta; Dassanayake, Priyanthi S.; Magpantay, Larry; Blyakher, Daniel; Regmi, Pratima; Von Behren, Julie; Martinez-Maza, Otoniel; Goldberg, Debbie; Spielfogel, Emma S.; Lacey, James V.; et al. (Frontiers in Epidemiology, 2025)
ObjectiveTo evaluate the associations between brominated flame retardants (BFRs), including polybrominated diphenyl ethers (PBDEs), exposure and circulating immune markers in a subset of women from the California Teachers Study cohort.MethodsIn this cross-sectional study, serum from 813 female participants in the California Teachers Study collected in 2013–2016 were evaluated for 11 BFR congeners and 16 immune markers. Three BFR congeners [BDE153 [2,2′,4,4′,5,5′-Hexabromodiphenyl ether], BDE47 [2,2′,4,4′-Tetrabromodiphenyl ether], PBB153 [2,2′,4,4′,5,5′-Hexabromobiphenyl]] had median levels that were above the level of detection and were further evaluated for associations with circulating immune markers. Odds ratios (OR) and 95% confidence intervals (CI) were calculated by a logistic regression model where BFR congeners (in quartiles) were associated with immune markers (dichotomized as above and below the respective median), adjusted for age and total lipids. Sensitivity analyses were also conducted evaluating BFR congeners as a continuous exposure (per pg/ml).ResultsAll participants had at least one of the 11 measured BFR congeners detected in their serum. Increasing levels of BDE47 were associated with elevated levels of BAFF (B-cell activating factor; ORQuartile 4 = 1.67, 95% CI = 1.11–2.51), soluble CD27 (sCD27, cluster of differentiation 27; ORQuartile 4 = 1.69, 95% CI = 1.12–2.55) and IL6 (interleukin 6; ORQuartile 4 = 1.74, 95% CI = 1.13–2.66). Increasing levels of PBB153 were associated with elevated levels of CXCL13 (chemokine ligand 13; ORQuartile 4 = 1.55, 95% CI = 1.02–2.35) but inversely associated with sCD27 (ORQuartile 4 = 0.57, 95% CI = 0.38–0.87). Results from continuous models of BFR were largely consistent. No associations were observed between BDE153 and any of the immune markers assessed.ConclusionsTwo BFR congeners were statistically associated with altered levels of circulating immune markers involved in B cell activation pathways; replication and further evaluation of these novel associations are warranted. If confirmed, our results add to the current literature regarding possible immune mechanisms by which BFR exposures contribute to immune-related health endpoints and conditions where B cell activation is prominent, including autoimmune conditions.